Arrest detention and criminal justice system: a study int he - Devi, B Uma (New Delhi, 2012)
This book critically examines the criminal justice system in India, focusing on interpretations by the Supreme Court of India. It also analyses the existing laws for arrest and detention and the constitutional validity of punitive measures.
Keywords: "Constitution on law, Arrest , Criminal justice administr"